Peran Hukum dalam Mendorong Pembangunan Ekonomi dan Menjamin Kesejahteraan Masyarakat : Perspektif Indonesia - Bahrul Ulum (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This article examines the important role of law in promoting economic development and ensuring the well-being of people in Indonesia. It analyzes the legal framework that governs economic activities, focusing on principles and regulations that facilitate economic growth, protect rights, and promote social justice. This article explores the evolution of Indonesia's legal system in response to economic challenges and opportunities, highlighting key laws and policies that have shaped the nation's economic landscape. This includes an analysis of the constitutional foundations of Indonesia's economic system, with a special emphasis on Article 33 of the 1945 Constitution, which mandates a "people's economy" based on the principles of kinship, cooperative ownership, and state control over vital resources. Furthermore, this article discusses the challenges and prospects of using the law as a tool to achieve sustainable and inclusive economic development. It emphasizes the importance of legal certainty, regulatory efficiency, and the protection of public interests in fostering a conducive investment climate and promoting equitable economic growth. The article also discusses the role of law in addressing important issues such as environmental protection, labor rights, and consumer protection, highlighting the linkages between economic development and social welfare. By examining Indonesia's experience, this article contributes to a deeper understanding of the complex relationship between law and economic development in the context of developing countries.